Family Female Directors versus Non‐family Female Directors: Effects on Firm Value and Dividend Payouts in an Extreme Institutional Environment. (5th June 2021) - Herdhayinta, Heyvon; Lau, James; Shen, Carl Hsin‐han
Abstract: By differentiating between family and non‐family female directors, this study aims to reconcile the prior mixed evidence on the effect of board gender diversity, especially when a company operates in a weak institutional environment. We argue that female directors are not homogenous. Drawing upon the socioemotional wealth perspective, this study proposes that family and non‐family female directors would display different behaviour when fulfilling their duty as monitoring managers. By analysing boards of directors in Indonesia from 2012 to 2018, we show that only non‐family female directors significantly enhance firm value and advocate dividend payouts. Our results indicate that non‐family female directors are more effective than family female directors at monitoring the management and protecting the interests of minority shareholders. This study echoes the call of integrating institutional contexts and differentiating different types of female directors when analysing the effects of gender diversity.